Sosialisasi Manajemen Pemasaran Berkelanjutan Melalui Edukasi Branding dan Digital Marketing pada UMKM Kuliner di Kota Palembang - Maiza Fikri; Fartina Destikarini; Faridatul Munawaroh; Hasan Pratama Putra; Januar Ida Wibowati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
This community service activity aims to strengthen the capacity of sustainable marketing management through branding and digital marketing education for culinary MSMEs in Pempek Village 26 Ilir, Palembang City, South Sumatra Province. The background to this activity is the condition of MSMEs that still face challenges in branding, limited digital literacy, and low awareness of sustainable practices. The implementation method was a participatory approach, including needs analysis, branding education, digital marketing training, mentoring, and evaluation using pre- and post-test instruments. The results of the activity showed a significant increase in participant understanding. The average pre-test score of 45 increased to 80 in the post-test, indicating an increase of over 30%. In terms of branding, participants began to understand the importance of business identity, brand narrative, and eco-friendly packaging design. In terms of digital marketing, MSMEs that were previously passive in their use of social media are now more active with consistent content strategies, utilization of marketplaces, and the use of QRIS-based digital payment systems. The integration of sustainability values ​​is also being implemented through brand narratives that emphasize tradition and environmental awareness. This activity has positive implications for increasing the competitiveness of culinary MSMEs in Palembang, both economically, socially, and environmentally. These findings confirm that academic intervention through community service can have a real impact on empowering MSMEs in the digital era.